Implementation of Standard Operating Procedures for Make Up Room for Guest Comfort at Hotel Grandhika Pemuda Semarang - Purnomo, Dedi; Putri Salsabila (Journal of Gastro Tourism, 2025)
This study aims to explain the implementation of Standard Operating Procedures (SOP) for making up rooms at Hotel Grandhika Pemuda Semarang with a focus on guest comfort. SOP for making up rooms is a work guideline that ensures that the cleaning and arranging of rooms are carried out according to the standards set by the hotel, thus providing a comfortable stay experience for guests. The research method uses a qualitative descriptive approach with data collection techniques through direct observation, interviews with supervisors, and documentation studies. The results of the study indicate that the implementation of SOP for making up rooms is consistently able to improve the cleanliness, tidiness, and comfort of hotel rooms. However, there are several obstacles, such as the lack of ongoing training for staff and time constraints in the cleaning process when the occupancy rate is high. The conclusion that can be drawn is that with optimization efforts through routine training, stricter supervision, and effective work time management. Implementation of good make up room SOP can increase guest comfort and the reputation of Hotel Grandhika Pemuda Semarang as a hotel that prioritizes service quality.